Distribution of light intensities of a solar bottle bulb - Bo-ot, Luis Maria T.; Redulla, Cherry Dara S. (2019)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/6703/5807
Keywords: Energy consumption; Energy conservation; Light source design & construction